Personal values in adolescence and sense of coherence in adulthood: A cross‐sectional study based on a retrospective recall - Naonori Yasuma; Kazuhiro Watanabe; Daisuke Nishi; Norito Kawakami (Wiley, 2020)
Abstract Aims The purpose of this study is to retrospectively examine the association between personal values in adolescence and sense of coherence (SOC) in adulthood. Methods J‐SHINE data from wave 1 (2010) and wave 3 (2017) were used in this study. We retrospectively measured personal values at age 15 in 2017 in two ways: (a) value priorities developed from Schwartz's theory of basic values; and (b) the commitment to values measured by Personal Values Questionnaire II (PVQ‐II). Multiple regression analysis was used to estimate the association. Results Having a value priority of belief, pursuing one's interest, enduring active challenges, cherishing family and friends, and having a commitment to values in adolescence were significantly and positively associated, while avoiding causing trouble was significantly and negatively associated with SOC in adulthood. Conclusions Personal values in adolescence may be associated with SOC in adulthood. Research of personal values in adolescence could contribute to the understanding the development of SOC.